2014
DOI: 10.1016/j.physc.2014.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the dynamics of skyrmions and superconducting vortices

Abstract: Vortices in type-II superconductors have attracted enormous attention as ideal systems in which to study nonequilibrium collective phenomena, since the self-ordering of the vortices competes with quenched disorder and thermal effects. Dynamic effects found in vortex systems include depinning, nonequilibrium phase transitions, creep, structural order-disorder transitions, and melting. Understanding vortex dynamics is also important for applications of superconductors which require the vortices either to remain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 60 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Up until now, however, analogous studies of skyrmion lattices have not been reported even though (as for superconducting vortices) it is well-known that defects and dislocations present in a sample can pin the motion of skyrmions induced by external perturbations such as an electric field [19] or a magnetic field [15]. This competition between disorder and elasticity will clearly give rise to a complex energy landscape promoting diverse metastable states [20], and superstructures [21,22]. Furthermore, up to now, previous imaging studies of skyrmion lattices could probe only the short range order due to limitations in the size of the imaged area and its homogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Up until now, however, analogous studies of skyrmion lattices have not been reported even though (as for superconducting vortices) it is well-known that defects and dislocations present in a sample can pin the motion of skyrmions induced by external perturbations such as an electric field [19] or a magnetic field [15]. This competition between disorder and elasticity will clearly give rise to a complex energy landscape promoting diverse metastable states [20], and superstructures [21,22]. Furthermore, up to now, previous imaging studies of skyrmion lattices could probe only the short range order due to limitations in the size of the imaged area and its homogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Using Thiele's approach [14,15], which treats skyrmions as rigid pointlike particles, equations of motion can be derived [10] that lend themselves to in-depth numerical simulations of interacting skyrmion systems. A similar treatment has been used to derive equations of motion for vortices in type-II superconductors [16,17], and the resulting equations are in fact quite similar to those for skyrmions [18], except for the Magnus force which is usually negligible in vortex dynamics. The Magnus force acts normal to the drift velocity of the skyrmion and can therefore cause orbits or spiraling trajectories.…”
mentioning
confidence: 99%
“…For example, such studies would help evaluate whether the vortex lattice may undergo a structural transition. These results may also shed light on understanding plasticity in other systems, including materials containing skyrmions [79][80][81], domain walls [82,83], and charge density waves [84,85].…”
Section: B Plastic Deformations Of the Vortex Latticementioning
confidence: 79%